Audit Quality and Auditor Switching in LQ45 Index Listed Firms of the Indonesia Stock Exchange - Chandra Prasadhita (Tirtayasa Ekonomika, 2021)
Auditor switching is important to maintain audit quality. This study aims to find empirical evidence regarding the effect of auditor switching on the audit quality of companies listed on the LQ45 index of the Indonesia Stock Exchange. Switching Public Accounting Firm and switching audit partner is the dependent variable in this study. Audit quality as the dependent variable is measured by the value of discretionary accruals. The saturated sampling method was used with the entire population of companies listed on the LQ45 index of the Indonesia Stock Exchange with a total of 45 companies in 2019 - 2020. Multiple regression analysis techniques were used. The results of the study stated that Public Accounting Firm switching and audit partners switching does not affect audit quality.Keywords : Public Accounting Firm Switching, Audit Partners Switching, Audit Quality.